The identity of Eritrichium heterocarpum Y.S.Lian & J.Q.Wang (Boraginaceae) - Hao, Jia-Chen; Ahmad, Latif; Zhou, Yu; Liu, Quan-Ru (Phytotaxa, 2017)
Based on consulting the original literature, examinations of specimens and field observations, Eritrichium heterocarpum Y.S.Lian & J.Q.Wang is shown to be conspecific with E. echinocaryum (I.M.Johnst.) Y.S.Lian & J.Q.Wang and is here formally treated as a synonym of the latter.